Characterization of Rice Husk for Graphene Extraction and Metallization - Onovo, Harrison Okechukwu; Agbeleye, Ademola Abiona; Akano, Theddeus Tochukwu; Oloyede, Olamilekan Razak; Oyegbami, Solomon Oaolapo; Amoo, Emmanuel Oluwatimilehin (ABUAD Journal of Engineering Research and Development (AJERD), 2024)
Rice husk, an underutilized agricultural waste product, serves as a potential precursor for graphene synthesis. This study focuses on synthesizing and characterizing graphene through the chemical exfoliation method, employing advanced analytical techniques to explore its potential applications in metallization. Graphene was produced by chemically activating rice husk ash (RHA) with potassium hydroxide (KOH) at 800 ºC. The extracted graphene underwent analysis using various techniques. X-ray Diffraction (XRD) confirmed the material's crystalline nature and graphitic structure. Fourier-Transform Infrared Spectroscopy (FTIR) identified typical functional groups present in the synthesized graphene. Raman Spectroscopy revealed significant defects and confirmed that the graphene consists of single or few-layer thin sheets. Transmission Electron Microscopy (TEM) showed the presence of thin graphene sheets and nanoparticles with sizes ranging from 1.47 nm to 5.80 nm. Ultraviolet-Visible Spectroscopy (UV-Vis) confirmed electronic structure and optical properties, essential for metallization. X-ray Fluorescence (XRF) confirmed the purity of the graphene, while Brunauer-Emmett-Teller (BET) analysis revealed a high specific surface area, making the material suitable for surface-based applications. Electrical conductivity tests demonstrated good conductivity in the lower to moderate current range. The study underscores the potential of rice husk-derived graphene for metallization, offering a cost-effective and eco-friendly synthesis method for industrial and commercial applications.